A systematic literature review on VR table manner innovation as an emerging learning media in culinary education - Aditia Gustiana Gunawan; Ence Surahman; Faiz Hilmawan Masyfa; Quinnera Putra Joshua (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
Virtual Reality (VR) is a significant innovation in culinary education, especially in table-service learning. This technology allows students to practice in a realistic virtual environment, creating an immersive and interactive learning experience. Through a Systematic Literature Review (SLR) of 50 articles, 13 from 2018 to 2025 were analysed to evaluate the effectiveness of VR. The results showed that VR can increase students' engagement, conceptual understanding, and technical skills in table service. VR also provides learning flexibility without time and place constraints. However, obstacles are challenging, including high costs, limited specific content, and psychomotor skill simulations. Therefore, integrating VR with conventional methods and educational institutions and the technology industry collaboration are crucial to optimise table-service learning and prepare students for the workforce.